RESVERATROL PROTECTS WHOLE BODY HEAT STRESS-INDUCED TESTICULAR DAMAGE IN RAT MODEL - ROY, PUJA; KUMAR, SOUMYA SUNDAR; MANNA, KRISHNENDU; DAS, ASIMA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The local thermoregulation in testis is important for optimum spermatozoa development. Excessive heat hampers this regulation resulting in alteration of normal testicular function. The present investigation confirms the role of free radicals in hyperthermia induced oxidative damage in testis and elucidates the dose-dependent ameliorating effect of resveratrol (RSV) against testicular oxidative damage. The aim of the present investigation is also to observe the role of selective concentration of RSV on heat induced oxidative changes in the damaged tissue. Methods: 48 male Wister rats were exposed to hyperthermic condition for the past 7 days of the total 21 days of experiment. RSV was pre- and co-treated with heat stress daily in a dose-dependent manner (1 mg, 5 mg, and 10 mg/kg body weight) for 21days. Results: Reactive oxygen species level was estimated using flow cytometry. Enhancement of hepatotoxicity markers in serum, lipid peroxidation and decreasing antioxidant status in the testis homogenate demonstrated that the oxidative damage in heat exposed tissue. Conclusion: Histological study along with biochemical and molecular assessment of the redox balance of testicular tissue in the present study revealed that RSV significantly ameliorated the heat induced damage in testis. The findings suggest that RSV is an effective antioxidant polyphenolic compound that can protect testis against hyperthermia induced oxidative damage.